SLIDING MODE CONTROL OF A CLASS OF MISMATCHED UNCERTAIN SYSTEMS - Ab Ghani, Mohd Ruddin (2002)
A proportional-integral sliding mode control is proposed for a system with mismatch uncertainties. The proposed controller gives robust stability for system in the presence of parameters variations, uncertainties and disturbances. A simulation study for as numerical example is given to illustrate the effectiveness of this control design.